Study Of The Availability Of Oriented Knowledge Economy In Syrian Organizations (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of this research is to determine the extent of the availability of knowledge economy orientation in the Syrian organizations; by determining the availability of orientation in the four knowledge economy pillars that developed by the World Bank to measure the knowledge economy index. These pillars are Education Resources - Innovation System - information and communication technology – and finally Economic Incentive and Institutional Regime. The research was done by collecting and analyzing data for a sample of 386 technical workers in Syria.The research has reached a set of results; the most important of which are: The Syrian computer society for Informatics provides a direction to the knowledge economy through two pillars of education and innovation, and it does not have a directive to the remaining two pillars. The final result indicates that there is a trend towards the knowledge economy in the studied organization.The research recommended the need for Syrian organizations to focus on the pillars of the knowledge economy in general, and the need to strengthen the approach of Syrian Scientific Informatics Society to knowledge economy by activating all the entrances to the pillars of the knowledge economy, such as focusing on increasing training, developing the work of technology incubators, as well as working on actual investment in technical competitions that participate It includes the members and employees of the mentioned association.